2021
DOI: 10.3390/w13192780
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Dynamics and Water Quality in the Venice Lagoon

Abstract: We analyzed the phytoplankton abundance and community structure monthly over a 20-year period (1998–2017) at five stations in the Venice lagoon (VL), one of the sites belonging to the Long-Term Ecological Research network of Italy (LTER-Italy). We focused on phytoplankton seasonal patterns, inter-annual variability and long-term trends in relation to water quality. Diatoms numerically dominated (ca. 60% on average), followed by nanoflagellates (37%), while coccolithophorids and dinoflagellates contributed less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Both belong to LTER-Italy (www.lteritalia.it; Bastianini et al, 2021;Camatti et al, 2021;Capotondi et al, 2021), the national Long-Term Ecological Research (LTER) network. We therefore have consistent data and knowledge, regarding phytoplankton assemblages and related abiotic factors in particular (Bernardi Aubry et al, 2012;Bernardi Aubry et al, 2013;Acri et al, 2020;Bernardi Aubry et al, 2020;Bernardi Aubry et al, 2021), which may provide useful background information for answering specific questions about the mechanisms that shape community structure. The LoV is separated from the GoV by two long barrier islands, water exchange with the sea being enabled by three wide inlets.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Both belong to LTER-Italy (www.lteritalia.it; Bastianini et al, 2021;Camatti et al, 2021;Capotondi et al, 2021), the national Long-Term Ecological Research (LTER) network. We therefore have consistent data and knowledge, regarding phytoplankton assemblages and related abiotic factors in particular (Bernardi Aubry et al, 2012;Bernardi Aubry et al, 2013;Acri et al, 2020;Bernardi Aubry et al, 2020;Bernardi Aubry et al, 2021), which may provide useful background information for answering specific questions about the mechanisms that shape community structure. The LoV is separated from the GoV by two long barrier islands, water exchange with the sea being enabled by three wide inlets.…”
Section: Introductionmentioning
confidence: 89%
“…We performed various types of analysis in order to: (i) identify the prevalent features and seasonal patterns of abiotic factors and chl a, (ii) assess and compare taxonomic composition and diversity at each station and (iii) identify the generalist and specialist taxa. We adopted a conventional division of the seasons (Bernardi Aubry et al, 2013;Bernardi Aubry et al, 2021) as follows: January-March = winter; April-June = spring; July-September = summer; October-December = autumn.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The haline stratification segregates phytoplankton at surface, triggering and controlling phytoplankton blooms, especially in the frontal area of the river delta (Mangoni et al, 2008). In general, it has been observed that total phytoplankton abundances decreased over the past two decades with a significant shift in 2003 (Cozzi and Giani, 2011;Djakovac et al, 2012;Bernardi Aubry et al, 2021), probably due to the reduction in the total load of freshwater discharge and related nutrient loads.…”
Section: Introductionmentioning
confidence: 99%